Influence of Helicobacter pylori, sex, and age on serum gastrin and pepsinogen concentrations in subjects without symptoms and patients with duodenal ulcers. Issue 6 (June 1993) - Mossi, S; Meyer-Wyss, B; Renner, E L; Merki, H S; Gamboni, G; Beglinger, C
Abstract : The relation between Helicobacter pylori (H pylori) infection and fasting gastrin and pepsinogen-I and -II concentrations was evaluated in 278 volunteers without symptoms and the results were compared with the values obtained in 35 patients with duodenal ulcers. H pylori infection was determined with the 13C-urea breath test in subjects without symptoms and with endoscopy, biopsy (histology and culture), and quick urease test (CLO-test) in patients with duodenal ulcers. Gastrin and pepsinogen-I and -II concentrations were assayed with specific radioimmunoassay systems. The results clearly indicate that fasting gastrin and pepsinogen-I and -II concentrations were significantly higher in H pylori positive compared with H pylori negative subjects. Neither age nor sex affected basal gastrin and pepsinogen concentrations in H pylori negative subjects. Fasting gastrin, pepsinogen-I and -II concentrations in serum samples were similar in H pylori positive persons with no symptoms and those with duodenal ulcers suggesting that similar mechanisms are involved in increasing plasma concentrations of these variables in both populations. Hypergastrinaemia and hyperpepsinogenaemia are therefore probably secondary to active H pylori infection.